Effectiveness of Government Services in Supporting Increased Agricultural Production - Muin, Sri Adrianti; Rahim, M.Akbar; Gunawan, Gunawan; Khusna, Dwi Asmaul (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This piece of work explores how well services to farmers provided by government affect agricultural production among farmers, and it takes a quantitative research method. Since agriculture along with the farmers plays a central role in national food security and rural livelihood, the intervention of the government which mostly intervenes to increase productivity in agriculture through extension services, irrigation support, training programs, and subsidies on production inputs have been a practice. This research used a cross-sectional survey research design, with stratified random sample of the farmers and the data were collected using structured questionnaires. Important variables were the kind and number of government service they received and reported differences in their agricultural yield. Descriptive statistics, Pearson correlation, and multiple regression analysis of data were observed. The findings indicate that the greatest influence on agricultural productivity is made by extension services which are significantly correlated (r = 0.966) and exhibited the largest regression coefficient (0.814). Other positives are subsidies, training and irrigation, although to a smaller extent. The regression model explains 96.6% of the y Var with all the means of government support supporting the same. Those results address major implications in the body of research by providing a comparative, empirical evaluation of various interventions in one model. The paper has indicated that in order to ensure sustainable agricultural growth, the policy factors should focus more on improving and expanding the extension systems and reevaluating the models of providing other services.